2023
DOI: 10.1136/bmjresp-2021-001187
|View full text |Cite
|
Sign up to set email alerts
|

Association between tobacco product use and asthma among US adults from the Population Assessment of Tobacco and Health (PATH) Study waves 2–4

Abstract: BackgroundResearch on cigarettes and adult asthma offers mixed findings, perhaps due to overlap with chronic obstructive pulmonary disease (COPD) and inadequate adjustment for other smoke exposures. Associations between other tobacco products, including e-cigarettes, and asthma are also understudied.Research questionUsing Population Assessment of Tobacco and Health Study waves 2–4 (2014/2015–2016/2017) data, we assessed the relation between tobacco product use and asthma in persons unlikely to have COPD.Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…Our sensitivity analysis among adults who did not have asthma or COPD showed a dose response association of P30D tobacco use with earlier age of asthma onset. These findings are in contrast with a 2014 to 2015 study 25 that started with adults without asthma aged 18 to 39 years and found that use of P30D ENDS or P30D use of any combustible product was not associated with asthma incidence 1 or 2 years later.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Our sensitivity analysis among adults who did not have asthma or COPD showed a dose response association of P30D tobacco use with earlier age of asthma onset. These findings are in contrast with a 2014 to 2015 study 25 that started with adults without asthma aged 18 to 39 years and found that use of P30D ENDS or P30D use of any combustible product was not associated with asthma incidence 1 or 2 years later.…”
Section: Discussioncontrasting
confidence: 98%
“…study 25 that started with adults without asthma aged 18 to 39 years and found that use of P30D ENDS or P30D use of any combustible product was not associated with asthma incidence 1 or 2 years later.…”
Section: Jama Network Open | Pulmonary Medicinementioning
confidence: 96%
See 1 more Smart Citation
“…Smoking is the second most significant risk factor (9.9%) for reducing the lifespan of asthma patients, amongst many other factors [ 3 ]. Compared with non-smokers, patients with smoking asthma experience poorer symptom control, a higher frequency of acute attacks, a more rapid decline in lung function, less effective ICS treatment, and a lack of guidance on a more efficient medication regimen, imposing a considerable burden on both patients and society [ 8 , 9 , 17 ]. In this study, we collected data from 190 patients suffering from smoking-asthma to explore the factors that could impact the level of symptom control after a 6 month period.…”
Section: Discussionmentioning
confidence: 99%
“…Since the proposal of the concept of ‘asthma control’ by the Global Initiative for Asthma (GINA) in 2006, ‘symptom control’ has been used as a measure to assess asthma and determine treatment options. It found that the mean asthma control test (ACT) score was about 1 point lower in combustible tobacco users compared with people who had never used tobacco (22.4 (SE=0.1) vs 23.6 (SE=0.2), P <0.01) [ 8 ].China is the world’s largest tobacco victim country - the smoking rate of people aged ≥15 years is as high as 26.6%, and the smoking rate of asthma patients is similar to that of ordinary people, which is 20-25%. However, in order to control for the influence of confounding factors and other potential mechanisms, a quantity of previous studies have excluded smoking asthma patients, resulting in a lack of progress in related studies on smoking asthma patients and a lack of targeted treatment guidance programs.…”
Section: Introductionmentioning
confidence: 99%